1999
DOI: 10.1034/j.1600-051x.1999.260702.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of Bio‐Oss®: a bovine‐derived xenograft for the treatment of periodontal osseous defects in humans

Abstract: The purpose of this study was to compare the bovine derived xenograft (BDX) Bio-Oss to demineralized freeze dried bone allograft (DFDBA) in human intrabony defects. 17 healthy patients with no systemic disease with moderate-severe periodontitis (7 males, 10 females; aged 34-67), were treated. Surgically, defects were included only if the intraosseous defect depth was >3.0 mm. Final selection included 30 defects. The sites were randomly assigned treatment with DFDBA or BDX. Soft tissue and osseous defect measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
95
4
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 17 publications
(20 reference statements)
17
95
4
7
Order By: Relevance
“…ABBM is an extensively researched material which has been successfully used alone for treatment of intra-bony and furcation defects, with a positive role in reducing PD, promoting CAL gain and enhancing defect fill in periodontal defects. 3,4,5,32 The positive results of the control group (ABBM alone) are in accordance with findings from previous studies which had failed to show significant differences between treatment with ABBM alone or combinations of ABBM with enamel matrix derivative or platelet-rich plasma (PRP). 30,39 Although the results of this study suggest that treatment with ABBM-PRF may not have provided significantly better results than those obtained with ABBM alone, the possibility for PRF to show any beneficial effects over the control group might have been masked by the fact that treatment with ABBM alone resulted in significant improvement.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…ABBM is an extensively researched material which has been successfully used alone for treatment of intra-bony and furcation defects, with a positive role in reducing PD, promoting CAL gain and enhancing defect fill in periodontal defects. 3,4,5,32 The positive results of the control group (ABBM alone) are in accordance with findings from previous studies which had failed to show significant differences between treatment with ABBM alone or combinations of ABBM with enamel matrix derivative or platelet-rich plasma (PRP). 30,39 Although the results of this study suggest that treatment with ABBM-PRF may not have provided significantly better results than those obtained with ABBM alone, the possibility for PRF to show any beneficial effects over the control group might have been masked by the fact that treatment with ABBM alone resulted in significant improvement.…”
supporting
confidence: 80%
“…These reductions were greater than those obtained in the present study. Conversely, Richardson et al 32 compared ABBM to demineralised, freeze-dried bone allograft (DFDBA) in human intra-bony defects and 6 months after surgery, the PD reduction was 3 mm for the ABBM group, which are lower compared to the reductions obtained in the present study. This discrepancy could be attributed to the differences in terms of study design, re-evaluation period, inclusion criteria, initial soft tissue measurements, initial defect depth and intra-bony defect configuration.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Clinical reports in the literature have demonstrated that BioOssÒ (BO), a bovine derived xenograft (BDX), in combination with or without membranes has supported periodontal regeneration in furcation and periodontal osseous defects. [12][13][14] Camelo et al and Mellonig presented histologic data indicating that the use of BO either alone or under a membrane may result in regeneration of the periodontal tissues. 15,16 In 2001, Houser et al clinically evaluated BO with a bioabsorbable collagen barrier, BG in the treatment of molar furcation defects.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of our research was to analyse the degree of bone regeneration in infrabony defects of the paUnauthenticated Download Date | 5/13/18 4:39 AM frabony periodontal defects six or more months after the application of various bone substituents (3,10,11,12,13). Lukovic and associates conducted a clinical study that showed Cerasorb and Bioss have similar efficacies as a treatment for deep infrabony pockets (14).…”
Section: Introductionmentioning
confidence: 99%